2011
DOI: 10.1007/s00428-011-1065-2
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of human epidermal growth factor receptor type-2 extracellular domain and cancer antigen 15–3 levels in needle washout fluid: a potential adjunct to the cytological diagnosis of breast cancer

Abstract: To determine whether the measurement of biomarkers in the needle washout fluid after fine needle aspiration cytology could strengthen cytological diagnosis, 29 benign lesions, 26 ductal carcinomas in situ (DCIS), and 95 invasive carcinomas of the breast were analyzed. Immediately after the aspiration samples were expelled onto glass slides, the needle was rinsed out with 2 ml of saline. Human epidermal growth factor receptor two extracellular domain (HER2-ECD) and cancer antigen 15-3 (CA 15-3) in the washout f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…First of all, CA153 in BS could be a promising biomarker for the diagnosis of early BC. Although relevant studies are so few that the diagnostic role of BS CA153 for BC cannot supported by a meta-analysis, two studies demonstrated CA153 in BS can discriminate early BC from healthy controls, indicating its diagnostic value for early-stage BC [ 10 , 14 ]. Second, the detection of CA153 in BS is safe and accessible.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…First of all, CA153 in BS could be a promising biomarker for the diagnosis of early BC. Although relevant studies are so few that the diagnostic role of BS CA153 for BC cannot supported by a meta-analysis, two studies demonstrated CA153 in BS can discriminate early BC from healthy controls, indicating its diagnostic value for early-stage BC [ 10 , 14 ]. Second, the detection of CA153 in BS is safe and accessible.…”
Section: Discussionmentioning
confidence: 99%
“…In theory, the higher the stage of breast cancer, the higher the CA153 concentration in breast secretions; the levels of CA153 in breast secretions would be significantly decreased after accepting effective treatments. One of the 5 primary studies showed an opposite result that the levels of CA153 in breast secretions from invasive breast cancer are lower than that from DCIS [ 10 ], which might result from the blockage of breast ducts during the breast cancer expansion. However, whether the levels of CA153 in breast secretions respond to any clinical treatment has not been reported.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations